3D animation for the raw beginner using Autodesk Maya - King, Roger (Roger Alan) (Boca Raton : CRC Press/Taylor & Francis Group, 2019)
"3D Animation for the Raw Beginner Using Maya is an ideal academic textbook as well as a superlative do-it-yourself training manual. When employed as a text, it frees the instructor from the painstaking task of developing step-by-step examples to present Maya's complex interface and basic capabilities. When used for individual study, aspiring animators revel in the book's easy-tofollow, hands-on learning style"--
An introduction to 3D modeling, animation, and rendering with a focus on autodesk Maya -- The gold standard of polygon modeling and the nurbs alternative -- A focus on simplicity : a core set of modeling tools in an overwhelming app -- Using the new(er) sculpting toolset in Maya in a polygon modeling workflow -- Advanced materials techniques : using Arnold mix materials and photoshop -- Advanced design techniques : modeling, composition, lighting, and materials -- Animation : particle dynamics, collisions, forces, blend shape, key-framing, skeletons, and scripting -- Rendering and lights
Includes index
1 10
Keywords: Computer animation -- Amateurs' manuals; Three-dimensional display systems -- Amateurs' manuals